1999
DOI: 10.1046/j.1365-2044.1999.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron versus placebo for the control of nausea and vomiting during Caesarean section under spinal anaesthesia

Abstract: SummaryThe vasoactive properties of EMLA (eutectic mixture of local anaesthetic) and amethocaine were compared using Doppler colour ultrasound to measure vein diameter in 20 male volunteers. EMLA or amethocaine cream were applied over veins on the dorsum of the hand and vein diameter was measured prior to application of the preparations and at 1, 1.5 and 2 h after removal. Visual analogue scores for skin colour and vasodilatation were performed at 1 h. The results showed no significant difference in vein diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 21 publications
4
27
0
1
Order By: Relevance
“…Further, the occurrence of nausea and vomiting during caesarean delivery are related to surgical manipulation of the uterus, abdominal visceras and peritoneum even in presence of adequate sensory-motor blockade. In our study, metoclopramide and ondansetron effectively reduce the emetic symptoms in caesarean section patients similar with the study of Lussos S et al (2) Abouleish E I et al (5) reported that the incidence of intra-operative vomiting (36%) was lower following administration of 4mg ondansetron iv during caesarean section under spinal anaesthesia compared to the control group (58%). In another study of Garcia Miguel F J et al (6) it was observed that ondansetron treated and metoclopramide treated patients experienced significantly fewer intra-operative nausea and vomiting episodes than placebo treated patients.…”
Section: Discussionsupporting
confidence: 89%
“…Further, the occurrence of nausea and vomiting during caesarean delivery are related to surgical manipulation of the uterus, abdominal visceras and peritoneum even in presence of adequate sensory-motor blockade. In our study, metoclopramide and ondansetron effectively reduce the emetic symptoms in caesarean section patients similar with the study of Lussos S et al (2) Abouleish E I et al (5) reported that the incidence of intra-operative vomiting (36%) was lower following administration of 4mg ondansetron iv during caesarean section under spinal anaesthesia compared to the control group (58%). In another study of Garcia Miguel F J et al (6) it was observed that ondansetron treated and metoclopramide treated patients experienced significantly fewer intra-operative nausea and vomiting episodes than placebo treated patients.…”
Section: Discussionsupporting
confidence: 89%
“…In clinical practice, it is commonly used at a dose of 4 mg intravenously 9,24-28 . Dershwitz et al studied 6 different doses of ondansetron for the prevention of PONV and they recommended the 4 mg dose as a result of their study 26. Abouleish et al found that use of 4 mg ondansetron during CS decreased the occurrence of the emetic symptoms significantly when compared with the placebo (%36 vs. %58) 24 . In our study we also used ondansetron at a dose of 4 mg and the emetic symptoms observed in Group O was similar to the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Flurbiprofen was significantly more effective in improving nausea and emesis than metoclopramide after 5 min (p \ 0.05). Effects on nausea and emesis did not significantly differ between flurbiprofen and droperidol, and between metoclopramide and droperidol measures applied [1][2][3][4][5][6][7][8][9][10][11]. Emetic symptoms have a complex and multifactorial etiology and can be influenced by age, gender, pain, operative procedure and anesthetic technique.…”
Section: Discussionmentioning
confidence: 99%
“…Nausea and emesis during regional anesthesia for elective cesarean delivery is widespread, with a reported occurrence of 17-80% of patients experiencing a nausea and/or emesis event [1][2][3][4][5][6][7][8][9][10][11]. Metoclopramide and droperidol are commonly administered to reduce nausea and emesis in patients undergoing spinal anesthesia for cesarean section [1][2][3]12].…”
Section: Introductionmentioning
confidence: 99%